The diagnostic yield of specimens obtained from endoscopic ultrasound guided fine needle biopsy of solid masses with the AcquireTM needle - Mark Bonnichsen; Ellie Skacel; James Kench; Arthur Kaffes; Payal Saxena (Society of Gastrointestinal Intervention, 2020)
Background: Recent developments in the design of needle tips used for fine needle biopsy via endoscopic ultrasound (EUS) allows for the procurement of core tissue for histological assessment in addition to cytology. Core tissue provides tissue architecture as well as the ability to perform molecular profiling investigations. We present a single centre study of experience with a new EUS needle with a Franseen tip (AcquireTM; Boston Scientific, Natick, MA, USA). The aim of the study was to assess the diagnostic yield of biopsies from solid lesions throughout the gastrointestinal tract. Methods: We performed a retrospective study of consecutive patients undergoing EUS biopsy between January 2017 and November 2018. Cystic lesions with no solid component were excluded or if samples were not sent for both cytology and histology. Rapid onsite evaluation (ROSE) was performed and the core tissue obtained was sent for histology. Results: Forty-six patients underwent EUS biopsy of solid lesions with specimens sent for both cytology and histology. Lesions included solid pancreatic masses (n = 31), lymph node (n = 3), gastric subepithelial lesion (n = 3), other (n = 9). The mean number of passes per lesion was 1.9 (range 1-4). In 43/46 (93%) of cases, a core specimen was obtained. Tissue obtained by EUS biopsy was adequate for evaluation by ROSE in 39/46 cases (85%). Histological diagnosis was confirmed in 41/46 (89%) cases compared to 31/46 (67%) cases with cytology (P = 0.011). Subgroup analysis of pancreatic lesions showed histological diagnosis was superior to cytology (90% vs 61%, P = 0.007). There were no adverse events. Conclusion: Histological analysis of specimens obtained via EUS biopsy was superior to cytology, particularly in assessment of solid pancreatic lesions